Risk factors for falls in the elderly - Alice Gabrielle de Sousa Costa; Thelma Leite de Araujo; Ana Railka de Souza Oliveira; Huana Carolina Cândido Morais; Viviane Martins da Silva; Marcos Venícios de Oliveira Lopes (Rev Rene)
The occurrence of falls represents an obstacle in the health of the elderly, and it contributes to increase their dependence. This study aimed to investigate the intrinsic and extrinsic risk factors, and possible statistical associations for falls in elderly people in the last six months. A case-control study with quantitative approach developed in three Rehabilitation Associations and one Social Assistance Center, with two groups with thirty participants each, a group with falls (case) and another group without falls (control). The data were collected from January to April 2010 by a form, and were organized is spreadsheets and analyzed by a statistical program. The case group presented worst intrinsic conditions and more extrinsic factors. Feet alterations, impaired balance and proprioceptive deficit were highlighted among the intrinsic risk factors that were statistically significant. The conclusion is the reinforcement of multifactorial hypothesis for falls occurrence with possibilities for nurse’s performance